2009
DOI: 10.1108/09685220910944768
|View full text |Cite
|
Sign up to set email alerts
|

Social engineering: assessing vulnerabilities in practice

Abstract: PurposeThe purpose of this paper is to investigate the level of susceptibility to social engineering amongst staff within a cooperating organisation.Design/methodology/approachAn e‐mail‐based experiment was conducted, in which 152 staff members were sent a message asking them to follow a link to an external web site and install a claimed software update. The message utilised a number of social engineering techniques, but was also designed to convey signs of a deception in order to alert security‐aware users. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…One reason for this lack of behavioural studies is that it is challenging to convince organizational managers to participate in studies in which their employees' actual behaviour is being measured. In the experiment conducted by Bakhshi et al (2009), a phishing mail was sent out to organizational employees as a mean to provide empirical evidence of how many employees succumb to social engineering. The experiment was ceased after approximately 3.5 h. During that period of time, 23 percent of recipients were fooled by the attack.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this lack of behavioural studies is that it is challenging to convince organizational managers to participate in studies in which their employees' actual behaviour is being measured. In the experiment conducted by Bakhshi et al (2009), a phishing mail was sent out to organizational employees as a mean to provide empirical evidence of how many employees succumb to social engineering. The experiment was ceased after approximately 3.5 h. During that period of time, 23 percent of recipients were fooled by the attack.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Bakhshi et al (2009), many users lack a baseline level of security awareness that is useful to protect them online. Naive users, who are not well-versed…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by [9] a phishing mail was sent out to organizational employees asking them to follow a link to an external web site and install a claimed software update. The experiment showed that 23 % of recipients were fooled by the attack.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, through a literature review we only found one study [6] that have examined if adding target-related information significantly increases the success of phishing. Furthermore, only [9] [10] have been conducted within an professional organization with employees that are not aware that they are participating in an security experiment in which their actual behavior is being observed. One explanation for this is that obtaining data of employees' actual behavior is a challenging endeavor [11].…”
mentioning
confidence: 99%